Antinociceptive & anti-inflammatory effects of Berberis vulgaris L. root's hydroalcoholic extract and determination of it’s possible antinociceptive mechanism in male mice - Mohebali, Shahrdad; Nasri, Sima; Kamalinejhad, Mohammad; Noori, Azam Sadat (Archives of Advances in Biosciences, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Berberis vulgaris L. (B. vulgaris) and specially its root have been used for a long time as a plant medicine in many countries including Iran. This plant is native in different parts of the world and is native in north areas of Iran like Khorasan. Recent research on this plant has shown its different therapeutic effects, Alkaloids especially Berberine has the most therapeutic usage among its compounds. This research is about the effects of Berberis vulgaris L. root's hydroalcoholic extract has done in two parts: its antinociceptive and anti-inflammatory effects was determined by Formalin and Xylene test respectively after determination of mortal plant dosage. Their dosage was 20, 40, 80 and 160 mg/kg. The three drugs include Naloxone 2 mg/kg, Dextromethorphan 20 mg/kg and L-NAME 10 mg/kg interact with more significant dosage of B. vulgaris. The results showed antinociceptive and anti-inflammatory effects of root’s extract of B. vulgaris in acute and chronic phases of Formalin test. The extract efficiency was analyzed in part two through Formalin test by three drugs individually and also by root’s extract. Conclusion: due to reduction of extract’s antinociceptive effect in both acute and chronic phases after Naloxone injection, it may concluded that the extract shows its signs through opioid receptors.